Patterns and Standards for Investigating Children and Youth in the Inquiry Official for Accuracy Fast and Fair - Khundiloknattawasa, Suwanna; Yoddamnoen, Chingtawan; Nakphoung, Aekalak (Community and Social Development Journal, 2020)
This research the purpose is to study extract knowledge and methods of investigative officers for correct and effective juvenile investigations and prepare a manual to investigate juvenile delinquency to the inquiry officials under the Royal Thai Police. To be used as a guideline for operations Is a qualitative research By using in-depth interviews with the sample population, Include Public prosecutor, Inquiry official, Almoner and Legal counsel 95 people and focus group discussion of 20 people. Content analysis. The study found that 1) The format and standards for the correct investigation. The inquirer must proceed correctly, completely, in accordance with the law, every step and have complete documentation for each offense. 2) The format and standards for quick investigation. The investigative officers must put the children in the judicial process must spend the least time. In which each case would have different difficulty there is no fixed format. And 3) Format and standards for fair investigation the inquiry official must act openly. Transparent, verifiable, without bias, providing equal opportunity for all parties no discrimination and legality do not use cruelty methods torture, coerce or deceive or convince the mind to act in any way. For this juvenile investigation guide the researcher brought knowledge that was developed into a manual for using as guideline to be easy to learn and practice.